Circular Economy as an Economic Model: Opportunities and Challenges - Mokhniuk, Anna (My University, 2025)
The circular economy serves as an economic model that emphasizes waste reduction and resource reuse, presenting opportunities such as cost savings, improved public relations, competitive advantage, and job creation. However, challenges include organizational culture, lack of information, financial constraints, inadequate legislation, low awareness, and limited customer interest. To sum up, successful implementation requires businesses to innovate their models and address internal barriers, contributing to a sustainable future while navigating the complexities of transitioning from a linear to a circular economy. Ultimately, embracing circular principles can lead to more resilient economies and a more sustainable future, but success will depend on overcoming structural barriers and fostering long-term commitment at all levels of society.
Keywords: Sustainable supply chains; waste reduction; resource reuse; 330.342.146:502.131.1:658.5